IMPROVING THE SPEED-STRENGTH TRAINING OF STUDENTS THROUGH TRACK AND FIELD EXERCISES (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the possibilities of improving the speed-strength training of students through the systematic use of track and field exercises in higher pedagogical education. Speed-strength qualities are among the most significant physical characteristics in the preparation of future specialists in physical education and sports because they determine the effectiveness of movement performance, athletic readiness, and the ability to master complex motor tasks. The study focuses on the pedagogical value of track and field exercises such as sprint running, standing long jumps, bounding drills, hurdle exercises, short-distance acceleration tasks, medicine ball activities, and plyometric elements in the development of explosive power, movement speed, coordination, and functional preparedness. The article argues that properly selected athletics-based exercises create favorable conditions for increasing students’ motor density in class, strengthening neuromuscular adaptation, and improving overall physical capacity. Special attention is given to methodological principles including gradual load progression, individualization, regular monitoring, and the integration of technical and physical training within one instructional process. The paper also highlights the role of track and field exercises in increasing students’ motivation, discipline, and engagement in physical education lessons. It is concluded that the pedagogically grounded inclusion of athletics exercises in the educational process significantly contributes to the development of speed-strength abilities and enhances the practical training of students in sports-oriented higher education.
Keywords: Track and field exercises, speed-strength training, students, physical education, explosive power, athletic preparedness, motor skills, pedagogical methods.